1981
DOI: 10.1108/eb024068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of online bibliographic searching on scientists' information style

Abstract: Industrial and academic users of online bibliographic searching over a year's time did not generally diminish their amount of use of other traditional manual means of information gathering activities. However, in comparison to less frequent users and nonusers, frequent users increased their reliance on librarians. Online users increased their appraisal of the adequacy of information services available to them, particularly as regards those aspects generally considered the primary benefits of online searching. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Bernal [1] did his pilot study on the use of scientific literature in Great Britain in 1948, there have been hundreds of studies which have investigated the information needs of users as well as the methods by which researchers obtain the information they need to conduct their research. Earlier studies that focused on the information needs and library use of scientists [2,3] social scientists [4][5][6][7] and humanists [8][9][10][11][12] contributed to the recent development of a discipline in information science that investigates the information seeking behavior of users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bernal [1] did his pilot study on the use of scientific literature in Great Britain in 1948, there have been hundreds of studies which have investigated the information needs of users as well as the methods by which researchers obtain the information they need to conduct their research. Earlier studies that focused on the information needs and library use of scientists [2,3] social scientists [4][5][6][7] and humanists [8][9][10][11][12] contributed to the recent development of a discipline in information science that investigates the information seeking behavior of users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Talking about approximately the same period (from the mid-1970s until the end of the decade), but from the angle of the scientist researcher's adoption and utilisation of online bibliographic searching technology, Bayer and Jahoda (1981) terised access to information is becoming more widespread, with an increase of 75% in the number of databases, a tripling of the number of records, and a quadrupling of the number of online searches. However, having found in their empirical study of the e¡ects of online bibliographic searching on scientists' information style, conducted over a year's time, that online searching did not generally diminish the amount of use of other traditional manual means of information gathering activities, they voice the then prevalent view that online searching was not meant to be substituted for the old manual approach, but merely to be added onto previous methods.…”
Section: Integration Of Technological Innovations Into the Information Seeking Work Of The Researchert He Groundbreaking Yearsmentioning
confidence: 99%
“…Much of the past research into the information behavior of life scientists and scientists in general has focused on the use of traditional, bibliographic resources (Bayer & Jahoda, 1981; Curtis, Weller, & Hurd, 1993, 1997; Dillon, 1981; French, 1990; Garvey, Tomita, & Woolf, 1974; Palmer, 1991a, 1991b; Rolinson, Meadows, & Smith, 1995; Skelton, 1973). These studies have shown that scientists value personal contacts as the first choice of information source, and ease of access to information.…”
Section: Introductionmentioning
confidence: 99%